Assessing Antibiotic Misuse: A Study on Knowledge, Attitudes, and Practices among the Population - Abdulrahman Saleh Hamad Alanazi, Mohammed Saleh H Alanazi, Amirah Farhan Gharreb Aljaysi, Jalilah Fallaj Maazir Alruwaili, Maha Munahi S Aldhafeeri, Hind Munif Khalaf Alshamari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This study aimed to assess the knowledge, attitudes, and practices (KAP) related to antimicrobial self-medication among a convenience sample of the populationMethodology: A descriptive cross-sectional study was conducted using a self-administered semi-structured questionnaire. A convenience sample of 359 participants provided appropriate consent for the study. The questionnaire comprised four sections: demographics, KAP regarding antimicrobial self-medication, professional medical knowledge, and attitudes of caregivers of children toward antimicrobial self-medication. The questionnaire was initially developed in English, translated into its final Arabic version, pilot-tested, and face-validated. Descriptive and quantitative analyses were performed using SPSS (V.20.0).Results: Approximately 64% (231) of the participants had used antibiotics without a prescription in the past 12 months, a practice significantly correlated with female gender and lack of knowledge. The primary reasons for self-medication were to save time and effort (109, 47%) and reluctance to visit doctors (89, 39%). Over 60% of participants used amoxicillin-clavulanic acid, with leftovers from previously prescribed medications and purchases from community pharmacies being the main sources of antibiotics. Among the 85 participants who were caregivers of young children, 18 (21%) reported administering antibiotics to their children without consulting a physician. Out of 115 participants claiming medical background, only 30 (26%) answered section 3 correctly, with 23 of them reporting antibiotic self-medication.Conclusion: This study revealed a notable inclination toward antibiotic self-medication among adults and children, which was not significantly reduced even among those with a medical background. The study highlights the need to address the underlying reasons for this practice to mitigate its prevalence